Ghosts be gone! - Jones, Marcia Thornton; Dadey, Debbie; Francis, Guy (New York : Scholastic, 2004)
It's Career Day and Andrew, the class bully, wants to be a rich and famous ghost hunter. Will the Ghostville ghosts be toast? Or will Andrew get himself slimed?
"A Little Apple paperback."
3.
007-010.
Keywords: Bullying -- Juvenile fiction; Bullying -- Fiction; Ghosts -- Fiction; Ghost stories